Different sensitivity and threshold in response to nitrogen addition in four alpine grasslands along a precipitation transect on the Northern Tibetan Plateau. Issue 17 (1st August 2019) - Zong, Ning; Zhao, Guangshuai; Shi, Peili
Abstract: The increase in atmospheric nitrogen (N) deposition has resulted in some terrestrial ecological changes. In order to identify the response of sensitive indicators to N input and estimate the sensitivity and saturation thresholds in alpine grasslands, we set up a series of multilevel N addition experiments in four types of alpine grasslands (alpine meadow [AM], alpine meadow‐steppe [AMS], alpine steppe [AS], and alpine desert‐steppe [ADS]) along with a decreasing precipitation gradient from east to west on the Northern Tibetan Plateau. N addition only had significant effects on species diversity in AMS, while had no effects on the other three alpine grasslands. Aboveground biomass of grasses and overall community in ADS were enhanced with increasing N addition, but such effects did not occur in AS. Legume biomass in ADS and AS showed similar unimodal patterns and exhibited a decreasing tend in AM. Regression fitting showed that the most sensitive functional groups were grasses, and the N saturation thresholds were 103, 115, 136, and 156 kg N hm −2 year −1 in AM, AMS, AS, and ADS, respectively. This suggests that alpine grasslands become more and more insensitive to N input with precipitation decrease. N saturation thresholds also negatively correlated with soil N availability. N sensitivity differences caused by precipitation and nutrient availability suggest that alpine grasslands along the precipitation gradient will respond differently to atmospheric N deposition in the future global change scenario. This different sensitivity should also be taken into consideration when using N fertilization to restore degraded grasslands. Abstract : A series of multilevel N addition experiments in four types alpine grasslands along a precipitation gradient on the Northern Tibetan Plateau were set up to identify the response of sensitive indicators to N input and estimate the sensitivity and saturation thresholds in alpine grasslands. Alpine grasslands become more and more insensitive to N input with precipitation decrease. Nitrogen saturation thresholds were controlled by rainfall amount and soil nutrient availability in different grasslands.